Plant blindness and children's recognition of plants as living things: a research in the primary schools context - Amprazis, Alexandros; Papadopoulou, Penelope; Malandrakis, George (Journal of biological education, 2021)
Children's conceptions of plants as living things are thoroughly analysed during the last decades. Additionally, many researchers showed interest in 'Plant Blindness', the people's tendency to ignore plants and underestimate them comparing to animals. Aim of this research is to validate plant blindness' intensity among Greek primary school students and clarify whether this phenomenon can be linked to the young students' recorded difficulty to recognise plants as living things. One thousand forty-eight primary students from both rural and urban areas of north Greece participated in our study. The instrument of our research was a questionnaire that mainly examined attitudes towards flora and students' consideration of plants as living things. According to the results, Greek students do find fauna more interesting than flora and plants are not being spontaneously recalled as living things. A relationship between students' preference in flora and their perception of plants as living things was found, along with several other significant correlations to variables such as gender, age and participation in environmental education projects. The findings of our study enhance the general concern about the reduced interest in plant life as this is determined in the context of the plant blindness hypothesis.